2013
DOI: 10.1186/1129-2377-14-24
|View full text |Cite
|
Sign up to set email alerts
|

The impact of headache and chronic musculoskeletal complaints on the risk of insomnia: longitudinal data from the Nord-Trøndelag health study

Abstract: BackgroundA strong relationship between insomnia and painful disorders has been found, but it is still unclear whether chronic pain leads to insomnia. There is a need of large-scale prospective studies to evaluate if there is a causal relationship between painful disorders and insomnia.MethodsAll inhabitants aged ≥ 20 years in Nord-Trøndelag County of Norway were invited to participate in two surveys (n = 92,566 and 93,860, respectively). 27,185 subjects participated in both surveys, and 19,271 of these were i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

7
56
0
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 75 publications
(65 citation statements)
references
References 36 publications
7
56
0
2
Order By: Relevance
“…A recent study reported that patients with insomnia had a higher prevalence of migraine than did patients without insomnia; interestingly, patients with migraine who had insomnia reported more headache-related disability (as measured by the Headache Impact Test [HIT-6]) than patients with migraine but without insomnia. 17 A recent review of sleep disorders and migraine 18 provides an excellent overview of research into the relationship between the 2. [13][14][15] The relationship may be bi-directional, however.…”
Section: Introductionmentioning
confidence: 99%
“…A recent study reported that patients with insomnia had a higher prevalence of migraine than did patients without insomnia; interestingly, patients with migraine who had insomnia reported more headache-related disability (as measured by the Headache Impact Test [HIT-6]) than patients with migraine but without insomnia. 17 A recent review of sleep disorders and migraine 18 provides an excellent overview of research into the relationship between the 2. [13][14][15] The relationship may be bi-directional, however.…”
Section: Introductionmentioning
confidence: 99%
“…1316 Interestingly, at least one report found that migraine and non-migraine headache were risk factors for later development of insomnia. 16 Bidirectional influences are likely though additional exploration is necessary.…”
Section: Introductionmentioning
confidence: 99%
“…1,2 Headache attacks are often precipitated by disturbed sleep (particularly when occurring in conjunction with high stress), 3 and sleeping helps resolve migraine attacks but can interfere with one's ability to maintain a consistent sleep schedule. Among these, sleep disorders are particularly common.…”
mentioning
confidence: 99%